2018
DOI: 10.1038/s41598-018-23775-8
|View full text |Cite
|
Sign up to set email alerts
|

Global Proteomics Deciphered Novel-Function of Osthole Against Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a progressive cardiovascular-disease with high mortality lacking high-efficiency drug. Our efforts attempted to delineate therapeutic action of osthole produced by Angelica Pubescens Maxim, which has the capacity to treat PAH by exploiting an iTRAQ-based proteomic method. Excitingly, osthole was observed to significantly restore 98 of 315 differential proteins significantly modified by PAH progression. They were primarily annotated into 24 signaling pathways. Four mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…In agreement with previous work, peroxisome proliferator-activated receptor (PPAR)-γ was identified as an important regulator of CTSS expression in SMCs [115,116]. Yao et al reported that osthole, a novel hypotensive agent purified from the Chinese medical plan Angelica pubescens Maxim, down-regulated MCT-induced CTSS levels while reducing PAH [117].…”
Section: Pulmonary Arterial Hypertension (Pah)supporting
confidence: 86%
“…In agreement with previous work, peroxisome proliferator-activated receptor (PPAR)-γ was identified as an important regulator of CTSS expression in SMCs [115,116]. Yao et al reported that osthole, a novel hypotensive agent purified from the Chinese medical plan Angelica pubescens Maxim, down-regulated MCT-induced CTSS levels while reducing PAH [117].…”
Section: Pulmonary Arterial Hypertension (Pah)supporting
confidence: 86%
“…A previous study exploited an iTRAQ-based proteomic method to investigate the therapeutic actions and associated mechanisms of osthole in rats with PAH induced by experimental monocrotaline (MCT). This study reported that the complement and coagulation cascade pathway was significantly disordered in PAH lungs [4]. In our sequencing data, within this pathway, the Kng1 and Thbd genes were the most significantly upregulated and downregulated genes, respectively.…”
Section: Discussionmentioning
confidence: 74%
“…Osthole is a natural coumarin present in the medicinal plant Cnidium monnieri. Because osthole demonstrates significant protective effects in animal models of hepatic diseases (30,31), cancer (54), diabetes (27,28), osteoarthritis (55), cardiovascular (56,57) and allergic diseases (18,34), it is a promising natural lead compound for drug discovery. Herein we demonstrate that osthole inhibits mast cell activation via MRGPRX2.…”
Section: Discussionmentioning
confidence: 99%